The Pedagogy of Witness. An Anthropological-Kreygmatic Perspective by Zbigniew Marek SJ & Anna Walulik CSFN – the Reflective Challenge for Education - Szymańska, Maria (Central European Journal of Educational Research, 2020)
Review of the book The pedagogy of witness. An anthropological-kreygmatic perspective, by Zbigniew Marek SJ & Anna Walulik CSFN